Humble Leadership: The Power of Relationships, Openness, and Trust (getAbstract Summary). - , getAbstract (linkedin.com, 2019)
The future of work requires a more personal style of leadership. Learn more about humble leadership in this audio-only summary of the book by Edgar H. and Peter A. Schein.